Radical–anion coupling through reagent design: hydroxylation of aryl halides. Issue 43 (28th October 2021) - Greener, Andrew J.; Ubysz, Patrycja; Owens-Ward, Will; Smith, George; Ocaña, Ivan; Whitwood, Adrian C.; Chechik, Victor; James, Michael J.
Abstract : The design and development of an oxime-based hydroxylation reagent, which can chemoselectively convert aryl halides (X = F, Cl, Br, I) into phenols under operationally simple, transition-metal-free conditions is described. Abstract : The design and development of an oxime-based hydroxylation reagent, which can chemoselectively convert aryl halides (X = F, Cl, Br, I) into phenols under operationally simple, transition-metal-free conditions is described. Key to the success of this approach was the identification of a reducing oxime anion which can interact and couple with open-shell aryl radicals. Experimental and computational studies support the proposed radical-nucleophilic substitution chain mechanism.